Seasonal patterns of methylmercury production, release, and degradation in profundal sediment of a hypereutrophic reservoir. (2nd October 2021) - Fuhrmann, Byran; Beutel, Marc; Ganguli, Priya; Zhao, Liying; Brower, Sarah; Funk, Andrew; Pasek, Jeffrey
Abstract: Fuhrmann B, Beutel M, Ganguli P, Zhao L, Brower S, Funk A, Pasek J. 2021. Seasonal patterns of methylmercury production, release, and degradation in profundal sediment of a hypereutrophic reservoir. Lake Reserv Manage. 37:360–377. Profundal lake sediment is an important site of toxic methylmercury (MeHg) production by anaerobic bacteria. This study tracked sediment MeHg cycling in hypereutrophic Hodges Reservoir, in the United States. Sediment-associated MeHg was most elevated in the early spring during moderately reduced conditions. In the late spring, MeHg and iron were released into hypolimnetic water during the progression from iron-reducing to sulfate-reducing conditions at the sediment–water interface. A decrease in porewater sulfate in the early summer indicated enhanced sulfate-reducing bacteria (SRB) activity and was associated with sediment buildup of MeHg, likely due to enhanced sorption to iron sulfides. Depletion of sulfate in the sediment during the fall corresponded with a substantial decrease in both sediment and water-column MeHg, suggesting that methanogenic conditions led to enhanced MeHg degradation. Shortly afterward, MeHg increased in the hypolimnion, indicating an upward shift in the zone of SRB methylation. Our study suggests 2 "hot moments" of MeHg entry into the water column, where it is susceptible to uptake into the pelagic food web: a spring window of mildly reduced conditions that promote MeHg release from sediment, and a fall window where MeHg is produced in the upper hypolimnion. These hot moments may potentially be managed to lower mercury bioaccumulation via redox enhancement of the profundal zone with approaches such as bottom water oxygenation, which began operation in Hodges Reservoir in 2020. However, the complexity of biogeochemical responses to such management perturbations in regard to MeHg cycling makes it difficult to predict the ultimate effect of oxygenation on mercury bioaccumulation. Supplemental data for this article is available online at https://doi.org/10.1080/10402381.2021.1940397 .